Perancangan Aplikasi Inventaris Gudang Menggunakan Bahasa Program PHP dan Database MySQL Berbasis WEB - Al Hakim, Aldie Lukman; Maulana, Ilham; Wafa, Itmamul; koswara, Yoga; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
CV. Gema Insani Press is a company that operates in the printing of books, calendars, books and so on. To support the production of goods, the role of the inventory warehouse is very important. The problem that often occurs is that the recording of incoming and outgoing goods is still using traditional methods using software from Microsoft Excel so that there is often an error in the amount of materials that makes the stock insufficient when needed. Therefore an application is needed that can help record incoming and outgoing goods from the warehouse so that the existing stock of materials is the same as the data entered. The development of this application uses a method that is often used, namely the waterfall method and the programming language used is PHP using MySQL as the database center. This application is can make it easier to record items in the warehouse.